2013
DOI: 10.1002/glia.22577
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic scratch injury in astrocytes triggers calcium influx to activate the JNK/c-Jun/AP-1 pathway and switch on GFAP expression

Abstract: Astrocyte activation is a hallmark of central nervous system injuries resulting in glial scar formation (astrogliosis). The activation of astrocytes involves metabolic and morphological changes with complex underlying mechanisms, which should be defined to provide targets for astrogliosis intervention. Astrogliosis is usually accompanied by an upregulation of glial fibrillary acidic protein (GFAP). Using an in vitro scratch injury model, we scratched primary cultures of cerebral cortical astrocytes and observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(96 citation statements)
references
References 109 publications
5
88
0
Order By: Relevance
“…65,67 A recent study showed that traumatic scratch injury to astrocytes triggers Ca 2 + influx, resulting in an increase in GFAP expression and increase in the size of glial scars. 68 It suggests that Ca 2 + provides the early injury signal that triggers the signal transduction cascades for astrogliosis through ER Ca 2 + store release and this is consistent with our results. We provided direct evidence of such a Ca 2 + pathway, and we further showed that activation of such Ca 2 + responses is heterogeneous, depending on the stimulus properties.…”
Section: Discussionsupporting
confidence: 91%
“…65,67 A recent study showed that traumatic scratch injury to astrocytes triggers Ca 2 + influx, resulting in an increase in GFAP expression and increase in the size of glial scars. 68 It suggests that Ca 2 + provides the early injury signal that triggers the signal transduction cascades for astrogliosis through ER Ca 2 + store release and this is consistent with our results. We provided direct evidence of such a Ca 2 + pathway, and we further showed that activation of such Ca 2 + responses is heterogeneous, depending on the stimulus properties.…”
Section: Discussionsupporting
confidence: 91%
“…The most crucial of elements in GFAP gene is a consensus AP-1 sequence, the binding site for the Fos and Jun families of transcription factors (Masood et al 1993). Gao et al reported that calcium influx triggered by scratch could activate the c-Jun/AP-1 signaling pathway to switch on GFAP expression (Gao et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The method we used to make a stab wound injury model was modified based on previous studies. [47][48][49] Mice were anesthetized by intraperitoneal injection of 4% chloral hydrate (1 mL/100 g). We use a needle diameter of 0.7 mm and the injury point was 2 mm left of themed line and 2.5 mm underneath the lambdoid suture (Fig.…”
Section: Animal Modelmentioning
confidence: 99%